ANALISIS PRODUKTIVITAS, PENDAPATAN DAN KESEJAHTERAAN PETANI KARET EKS UPP TCSDP PENGHIDUPAN DI DESA BINA BARU KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Millia Aldavira; Syaiful Hadi; Ahmad Rifai (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims to analyze the productivity, revenue, households income structure, pattern of households expenditure, and welfare of households of the smallholder rubber plantation of ex-TCSDP development. Research was done by survey at Bina Baru Village. Data were collected from 30 small-holders rubber farmers using purposive sampling. Analysis of the results showed that the productivity of smallholder rubber plantation as 2.39 ton/ha/yearequivalent lump, the revenues of samallholder rubber plantation as Rp. 22.602.447/ha/year. The structure of household income derived from agriculture is 87,59 percent and 12,41 percent for non-agricultural income. The pattern of household expenditure shown that the food expenditure as 38,58percent and non-food expenditures as 61,42 percent. Result also show that the household of the smallholder rubber plantation at Bina Baru Village have the total expenditure more than 320 kg of rice equivalent. The household of small-holders rubber plantation have the total expenditure above the poverty line (Rp.336.681/capita/month). The household welfare using the 14 indicators of relative poverty by Indonesian Statistic show that 66,67 percent household have ability to fullfill the basic need or prosperous, while 33,33 percent is almost prosperous. Keywords: Smallholder RubberFarmer, Productivity, Income,Welfare